Penggunaan Kotak Kayu Batas Awalan Lompat Jauh untuk Meningkatkan Ketepatan Kaki dalam Menolak - Raden Mamat Rahmat (Jurnal Syntax Transformation, 2021)
The purpose of this study was to find out how pebting the use of wooden box long jump prefixes to improve foot accuracy in resisting. Research design in this study using Class Action Research (PTK), The author conducted class action research by going through 2 cycles, each cycle 2 meetings. The first meeting of the learning process as usual, during the practice of a series of long jump movements, students take turns jumping. The Observer notes the correct jumpers and those who failed in the jump. The teacher assesses the quality of the student's motion from the prefix until it lands. As a result of the observations, the correct students (not failing) repulsion only reached 52.5%. The assessment results of the new student process reached an average score of 46 and 87.5% still below KKM (78). The second meeting of cycle 1, true repulsion reached 60% and the process assessment results reached an average score of 47 and 85% still below KKM(78). In the second cycle there is a different treatment from the first cycle, which is when the student after the first jump or before making the jump, the student checks the mark first, the step starts from the reject board to the prefix area and in the last step the student marks the batas with a woodenbeam. From such efforts, the first meeting of the second cycle, true repulsion reached 80% of the number of participants and the results of the assessment process reached an average score of 66 and those who achieved a KKM score or more increased to 45%. At the last meeting of the second cycle at different times with the same treatment the repulsion resulted in a 100% repulsion. from the number of participants present and the results of the assessment process reached an average score of 83 and 100% of students achieved KKM (78). So the conclusion that using wooden boxes for long jump start limits hanging style can improve foot accuracy in resisting and improve the results of the learning process so that the value of KKM can be achieved and exceeded.